2010
DOI: 10.1007/s11136-010-9739-9
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in adult survivors of cancer during adolescence: what contributes to the latter satisfaction with life?

Abstract: Adult survivors of cancer with onset during adolescence are experiencing less LS than the general population. Long-term routine follow-up visits are recommended to identify persisting effects of cancer survival on LS and to provide support for those with special needs. Physicians need to pay special attention to potential risk factors such as psychological distress, somatic late effects, persistent psychological distress, and a lack of posttraumatic growth, which are negatively correlated with LS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 64 publications
3
63
0
3
Order By: Relevance
“…All but one participant reported that they experienced at least one positive aspect of being treated for cancer. Quantitative research examining the prevalence of PTG in AYA cancer populations is scarce but suggests that most AYA cancer patients report some PTG [1216]. …”
Section: Introductionmentioning
confidence: 99%
“…All but one participant reported that they experienced at least one positive aspect of being treated for cancer. Quantitative research examining the prevalence of PTG in AYA cancer populations is scarce but suggests that most AYA cancer patients report some PTG [1216]. …”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this, a number of studies have suggested that children and adolescents affected by cancer are no more likely to develop post‐traumatic stress symptoms (PTSS) than are healthy peers . In fact, several studies have found that compared with normative samples, children affected by cancer experience greater adjustment and quality of life, and lower anxiety and PTSS …”
Section: Introductionmentioning
confidence: 99%
“…From 2006 to 2010, 5 studies with external cooperation partners were conducted at the GCCR [e. g. 7,8,9,28,29] . Between 156 and 4 685 patients were contacted.…”
Section: External Cooperation Projectsmentioning
confidence: 99%